PENGARUH IKLIM ORGANISASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA PT. SURYA MUSTIKA LAMPUNG CABANG BATURAJA - Darman Syafe'i; Aneka Apriani (Jurnal Manajemen Bisnis Unbara, 2023)
ABSTRACT This Study aims to The influence of Organization Climate and Career Development on Employees’ Performance at PT. Surya Mustika Lampung Baturaja The population in this study was 38 employees at PT. Surya Mustika Lampung Baturaja. The analytical method used is a quantitative method using the Multiple Linear Regression analysis tool. The results of the analysis explain each of the Organizational Climate variables () is 2,439 and Career Development () is 4,141 greater than the value of 2,030 stating all variables influence the Employees’ Performance at PT. Surya Mustika Lampung Baturaja with a calculated F value of 22.619 greater than F table of 3.27 states that together all variables Influence Climate and Career Development influence Employees’ Performance at PT. Surya Mustika Lampung Baturaja. The value of the coefficient of determination (R Square) is 0.564 meaning that in this case the contribution of Climate and Career Development is 56.4%, while the remaining 43.6% is influenced by other variables.